Beyond glycan barriers: non-cognate ligands and protein mimicry approaches to elicit broadly neutralizing antibodies for HIV-1 - Walimbwa, Stephen Ian; Maly, Petr; Kafkova, Leona Raskova; Raska, Milan (Journal of biomedical science, 2024)
Human immunodeficiency virus type 1 (HIV-1) vaccine immunogens capable of inducing broadly neutralizing antibodies (bNAbs) remain obscure. HIV-1 evades immune responses through enormous diversity and hides its conserved vulnerable epitopes on the envelope glycoprotein (Env) by displaying an extensive immunodominant glycan shield. In elite HIV-1 viremic controllers, glycan-dependent bNAbs targeting conserved Env epitopes have been isolated and are utilized as vaccine design templates. However, immunological tolerance mechanisms limit the development of these antibodies in the general population. The well characterized bNAbs monoclonal variants frequently exhibit extensive levels of somatic hypermutation, a long third heavy chain complementary determining region, or a short third light chain complementarity determining region, and some exhibit poly-reactivity to autoantigens. This review elaborates on the obstacles to engaging and manipulating the Env glycoprotein as an effective immunogen and describes an alternative reverse vaccinology approach to develop a novel category of bNAb-epitope-derived non-cognate immunogens for HIV-1 vaccine design.
Keywords: Non-cognate ligands; neutralizující protilátky; polysacharidy; genové produkty env - virus lidské imunodeficience; ligandy; Molecular Mimicry; vakcíny proti AIDS; HIV-1; HIV infekce; HIV Antibodies; Combinatorial protein library; Glycans; Protein mimicry; Antibodies, Neutralizing; env Gene Products, Human Immunodeficiency Virus; Ligands; Humans; HIV-1 vaccine; Broadly neutralizing antibodies; molekulární mimikry; AIDS Vaccines; Polysaccharides; HIV Infections; Epitopes; HIV protilátky; lidé; epitopy